Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal pada Konsep Kesebangunan Berdasarkan Newman Error Analysis - Putri, Nurmala Setianing; Al Jupri (Papanda, 2025)
This research is classified as descriptive qualitative research. The type of research is a case study. The subjects in this study were three students in the Geometry of Plane and Space course. The research instrument used was a question related to the concept of similarity, along with Newman's error analysis sheet, to identify the type of error. The data analysis technique used was to identify and classify errors in students' answers related to questions on the concept of similarity. According to Newman, the answers were further analyzed to describe the types of errors that arise from each category and formulate alternative solutions that can be done to overcome the various types of errors. Based on Newman Error Analysis, the types of errors experienced by students include Comprehension Errors, Transformation Errors, and Process Skills Errors. These types of errors are related to students' lack of understanding regarding the requirements for two triangles to be said to be similar; students are less skilled when carrying out the proof process, which requires supporting information when stating a statement in the proof process, and students' lack of mastery in using the Pythagorean Theorem. Alternative solutions include emphasizing several key aspects related to the concept of similarity, both in terms of the conditions for two triangles to be considered similar and the application of the similarity theorem. It requires considerable practice in constructing mathematical proofs and utilizing the Pythagorean Theorem. Recommendations for subsequent researchers include exploring the types of errors in the concept of similarity in more varied contexts.